The Gambia : Fragility Risk and Resilience Assessment - African Development Bank; World Bank Group (World Bank, Washington, DC, 2017)
This analysis explores the causes of state fragility in The Gambia and identifies priority policy actions to bolster macroeconomic stability and reinforce the resilience of public institutions. In countries in fragile situations, a carefully targeted engagement strategy can have a transformative impact, and appropriate external assistance can mark the difference between the restoration of a functional public sector and a descent into a vicious cycle of institutional failure and conflict. Given the pivotal importance of engagement in countries in fragile situations, the African Development Bank (AfDB) and the World Bank’s Macroeconomics and Fiscal Management Global Practice (MFM-GP) are striving to better understand the factors driving fragility in The Gambia and formulate a strategic approach to policy support, development programming, and project design that reflects the country’s unique political, economic, and institutional circumstances. This report is the product of a collaboration between the MFM-GP and the AfDB’s Transition Support Department. The analysis was undertaken at a particularly critical moment in The Gambia’s history, as the 22-year rule of former President Yahya Jammeh gives way to the democratically elected administration of President Adama Barrow. The new government has struggled to address the political, social, and economic turbulence generated by the transition, by a legacy of mismanagement, and by climatic shocks. The World Bank and AfDB teams conducted a joint Fragility and Resilience Mission in Banjul and Dakar between February 24 and March 9, 2017. The mission’s objective was to evaluate the rapidly evolving political and economic situation in the aftermath of the presidential election and to discuss with government and civil-society stakeholders the issues identified in previous analyses. The mission findings formed the basis for a comprehensive assessment of political, social, and economic dynamics in The Gambia, including its external and domestic vulnerabilities, the capacity limitations of its public sector, potential sources of conflict, and priority areas for engagement by the international development community.